Evaluación administrativa, mediante la aplicación de la metodología Canvas, para proponer el plan de negocios en el Hostal Jireh, en la ciudad matriz del cantón Tena, provincia de Napo - Sánchez Yauripoma, Sandra Milena (2016)
The city of Canton Tena matrix has a variety of hotels including hotels of different categories. Hostel Jireh doesn`t have a business plan that lets know the market to which it is addressed and to establish obtectives and strategies that improve service, quality and income economical. This is the reason for tourists who visit the city don`t know about the existence of this hostel and in case tourists visit the hostel, the do not wish to come back and prefer to choose another place to stay. This research study seeks to find solution to the problem with the “administrative evaluation, through the application of the CANVAS methodology to propose the business plan at the hostel Jireh, in the Matrix Canton Tena, Province of Napo.” For which the followings objetives were established: conduct the situational diagnose of the study area; set the administrative evaluation of hostel Jireh through the application of the CANVAS methodology; determine the desing of the business plan of hostel Jireh and organize the socialization of business plan. The desingn of the research was not experimental and of field, the method was used inductive-deductive and statistical, as research tools, forms were made to keep inventory of tourists and 123 surveys were performed among tourists and inhabitants, among the most relevant results, it was found that the business plan offers a net income of $ 57.565, 54 years, for which it is determined that the application of this methodology is beneficial and generates growth for this hostel. It is determining a VAN of $ 186.489,81 and an TIR of 71 %. Which establishes as a final conclusion that the realization of this proposal is feasible.